2018
DOI: 10.1039/c8ta01019f
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures and enhanced photocatalytic properties of blue phosphorene/BSe van der Waals heterostructures

Abstract: Constructing van der Waals heterostructures can enhance two-dimensional (2D) materials with desired properties and greatly extend the applications of the original materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(112 citation statements)
references
References 60 publications
5
107
0
Order By: Relevance
“…where r g-GaN/BlueP , r BlueP , and r g-GaN are the total charge density of the heterostructure, charge density of monolayered BlueP, and charge density of g-GaN, respectively. 5 For the investigation on the optical-absorption ability of the heterostructure, the absorption coefficient was calculated using…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where r g-GaN/BlueP , r BlueP , and r g-GaN are the total charge density of the heterostructure, charge density of monolayered BlueP, and charge density of g-GaN, respectively. 5 For the investigation on the optical-absorption ability of the heterostructure, the absorption coefficient was calculated using…”
Section: Methodsmentioning
confidence: 99%
“…Many strategies have been put in place to advance "green" technologies, and the development of photocatalysts for water splitting is considered to be a promising measure because these catalysts can break down water into hydrogen (H 2 ) and oxygen (O 2 ) under the illumination of visible light to produce sustainable and renewable energy. 1 As photoelectrochemical (PEC) water splitting by semiconductors attracts more and more attention, [2][3][4][5] it has been reported that a crucial requirement for water splitting is a suitable band edge of the semiconductor, 1,6 where the conductionband minimum (CBM) of the material should be greater than the reduction potential (À4.44 eV) for H + /H 2 , and the valenceband maximum (VBM) of the material should be less than the oxidation potential (À5.67 eV) for O 2 /H 2 O, 7 which means the bandgap of any qualied photocatalyst should be more than 1.23 eV. 8 Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The vdWs corrections in GaS/C 2 N heterostructure and the monolayers were treated by applying DFT-D2 method of Grimme [54]. This method has been demonstrated to give a reliable description of the vdW heterostructures [55,56]. The electronic configurations of C (2s 2 2p 2 ), S (3s 2 3p 4 ) and Ga (3d 10 4s 2 4p 1 ) are treated as the valence electrons.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Loading 2D materials on varied substrates can mechanically modulate bandgaps and band edges of 2D materials . Thus, it is of great importance to discuss the influence on the band edges and bandgaps of CdCHTs caused by strains.…”
Section: Resultsmentioning
confidence: 99%